Pengaruh Pemberian Pupuk Kandang Kotoran Ayam dan Pupuk NPK Mutiara Yaramila Terhadap Pertumbuhan dan Hasil Tanaman Terung (Solanum Melongena L.) pada Tanah Berpasir - Mohammad Hertos (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The purpose of this research was to find Chicken Manure and NPK Mutiara Yaramila Fertilizer on the growth and yield eggplant (Solanum melongena L.) in sandy soil. The research was arranged in a Completely Randomized Design with two factors and three duplications. The first factor was to find chicken manure (K) on the three levels : 20 ton/ha (K1), 30 ton/ha (K2) and 40 ton/ha (K3), the second factor was NPK Mutiara Yaramila Fertilizer (Y) on the three level : 200 kg/ha (Y1), 300 kg/ha (Y2) and 400 kg/ha (Y3). The results show the experimental treatments of chicken manure and NPK Mutiara Yaramila Fertilizer was significantly on the parameters: plant high, number of leaves, number of productive branches, number of fruit and weight of fruit. The highest yield to parameters of plant high in old 2, 4 and 6 MST (25,30 cm, 36,37 cm and 60,83 cm) number of leaf in old 2, 4 and 6 MST (8,67 sheet, 11,00 sheet and 23,33 sheet), number of productive branches (8,67 branches), number of fruit (4,33 fruits) and weight of fruit (417,23 g), obtainable on the treatments to find chicken manure as big as 40 ton/ha and NPK Mutiara Yaramila Fertilizer as big as 300 kg/ha.